[18F]FDG PET/CT versus [18F]FDG PET/MRI in the diagnosis of lymph node metastasis in nasopharyngeal carcinoma: a systematic review and meta-analysis - Lei, Junfang; Li, Xu; Xue, Wenbo; Qian, Xinrui; Wang, Tong; Xiang, Yunuo; Zhang, Yangchun; Chen, Meixing; Liu, Zhaohui (Frontiers in Medicine, 2024)
Purpose This meta-analysis aimed to evaluate the comparative diagnostic accuracy of [18F]FDG PET/CT versus [18F]FDG PET/MRI in identifying lymph node metastases in individuals with nasopharyngeal carcinoma. Methods A comprehensive search was executed across PubMed, Embase, and Web of Science through September 2023 to identify studies evaluating the diagnostic precision of [18F]FDG PET/CT and [18F]FDG PET/MRI in detecting lymph node metastasis in nasopharyngeal carcinoma. Sensitivity and specificity were assessed through the DerSimonian-Laird method, incorporating the Freeman-Tukey transformation. Results The meta-analysis encompassed nine articles, involving a total of 916 patients. The overall sensitivity and specificity of [18F]FDG PET were 0.95 (95%CI: 0.88–1.00) and 0.95 (95%CI: 0.84–1.00). The overall sensitivity of [18F]FDG PET/CT was 0.94 (95%CI, 0.85–0.99), whereas [18F]FDG PET/MRI achieved a sensitivity of 1.00 (95%CI, 0.94–1.00). The findings reveal that [18F]FDG PET/CT demonstrates comparable sensitivity to [18F]FDG PET/MRI (p = 0.20). The overall specificity of [18F]FDG PET/CT was 0.94 (95%CI, 0.82–1.00), whereas [18F]FDG PET/MRI exhibited a specificity of 0.98 (95%CI, 0.93–1.00). Additionally, the results suggest that [18F]FDG PET/CT offers similar specificity to [18F]FDG PET/MRI (p = 0.11). Conclusion [18F]FDG PET demonstrates high sensitivity and specificity in identifying lymph node metastasis in nasopharyngeal carcinoma. Furthermore, [18F]FDG PET/CT exhibits comparable sensitivity and specificity to [18F]FDG PET/MRI. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=496006, PROSPERO (CRD42024496006).